Perancangan Sistem Android Pemberitahuan Absensi Dan Pengumuman Untuk Orang Tua Wali Murid Pada Smk 2 Mei Bandar Lampung - Hengki Fernando; Iin Marliana; Adijaya Saputra; Apriliani Taurusia; Emi Susanti (Jurnal Teknologi dan Informatika (JEDA), 2023)
This study aims to design an android system of attendance notifications and announcements for parents of student guardians at May 2 SMK Bandar Lampung. This type of research is classified into descriptive research, namely a study that examines the status, group or organization and the object of the system state of mind from current events, so that there is a systematic picture. Data collection techniques use techniques as follows: observation or observation, interviews and literature study. The results of the research Every Parent Guardian students can find out the development of their son or daughter in school. The school can provide notification information about student attendance data with the system.